TINJAUAN KHIYAR TERHADAP PERTANGGUNGJAWABAN PENJUAL ONLINE TERHADAP BARANG YANG CACAT - Nikmah Dalimunthe (State of Islamic Institute Langsa, 2019)
This articles explores the accountability of online sellers on goods defects at their trades. This phenomenon is now growing rapidly. It’s so loved by all people mostly. Ease in transcastions and facilitating of buyer to get the desired item from seller is the main selling power. But, from the overall activity, the lack of awareness and understanding of buyers about merchandise selection and checking, often used as an opportunity by seller to give the goods inappropriate trades. Buyer get inappropriate items, either from size, color, brand to defects of goods received. In fiqh, the buying and selling process requires four conditions: Sighat al-’aqd, Mahallul ‘aqd, Al’aqidaian and Maudhu’ul ’aqd. That conditions indicate the existence of seller’s accountability to the buyer for his merchandise, including online shop. So, the seller must fulfill the terms of trading as a form of responsibility in every transaction, both conventional and online shopping